BENDEL KESLINGMAS NO 123 TAHUN 2014 - Sri, syukron Ika, Tofiq Faiza, dkk (Poltekkes Kemenkes Semarang, 2014)
Pb is one of the air pollutants from motor vehicle combustion. The amount of Pb in the air can affect the surrounding environment include snack foods sold at roadside. The purpose of this study was to determine the levels of lead (Pb) in the snack food, sanitary conditions at street vendors as well as the density of vehicles on Jalan H.R. Bunyamin Purwokerto North Year 2014. The method used is descriptive research is to reveal the levels of lead (Pb) in the snack food, sanitary conditions at the street vendors as well as the density of vehicles on Jalan H.R. Bunyamin Purwokerto North Year 2014. The results obtained from this research that dumplings before exposure to 37 x 10-6 ppm and after exposure to 45 x 10-6 ppm, bakwan before exposure to 53 x 10-6 ppm and after exposure to 75 x 10-6 ppm, eclairs before 52 x 10-6 ppm exposure and after exposure to 67 x 10-6 ppm for 6.5 hours with exposure obtained results are still below the threshold value of the ISO 7387:2009 maximum limit of heavy metal contamination in food is 0:25 ppm. Sanitary conditions snack food outlets are categorized either by value 90.9% and 81.8%. As for the density of vehicles in the vicinity of the current is stable for motorcycles and cars are free to flow. Conclusions and suggestions of this study was to have been an increase in the levels of lead (Pb) on street food hawkers in Jalan H.R. Bunyamin Purwokerto North but is still below the threshold value and is safe for consumption by the purchaser. Sellers pay more attention street food presented in a position when the container is opened and immediately closed again when the buyer is no longer choose snack foods, giving feedback on the seller through a distributor for wrapping/ packing snack food for sale as well as the provision of food supply storefront in place. References : 21 (1992-2014)